PENGGUNAAN MATA UANG DINAR DAN DIRHAM SEBAGAI SOLUSI PREDIKSI KRISIS MONETER DI INDONESIA - Shifa, Mutiara; Amalia, Alfi; Abd.Majid, M.Shabri; Marliyah, Marliyah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
One of the main sources of the currency crisis experienced by Indonesia is the use of paper money that is not backed by gold. The data analysis technique used in this research is descriptive qualitative analysis, which is a method of data analysis by describing the description/conclusion of the use of the dinar and dirham currencies as a solution to the global economic crisis. The results of the research on the Dinar currency are a solution to the impact of using legal tenders in the world economy. because fiat currency will cause instability in the world economy, then to overcome this stable currency is the gold dinar. In the year 250m/648 H, the dinar was used as currency. Apart from being a currency, the dinar currency can also prevent currency depreciation. The Dinar is a stable currency. Why is that? Since the time of the Prophet Muhammad, the dinar currency has never experienced inflation or deflation. And the dinar is also made of gold. Gold prices remain stable. Even if there is a crisis in a country, the price of gold will remain stable. It has a stable value in every country and can promote domestic and international transactions. Dinar can also reduce speculation, manipulation and arbitrage. Dinar currency with the same value will be able to affect the level of speculation and arbitrage in the foreign exchange market, because differences in currency values will be difficult to occur. Dinar can also minimize recession and economic recession. Using the dinar in a country can also minimize the currency risk the country faces.